Effects of Supplementation with Different Nutrient Contents of Vitamin E Diets on the Performance and Health Status of IPB-D3 Candidate Chicken Strains - Romantis, Sara; Sumiati; Sumantri, Cece (Faculty of Animal Science, Universitas Brawijaya, 2024)
The purpose of this study was to evaluate the effect of supplementation with 200 ppm vitamin E in a diet with different nutrient contents on the performance and health status of the IPD-D3 candidate chicken strain. This research used 160 IPB-D3 chickens that were reared for 5 to 12 weeks. This experiment used a completely randomized factorial design with 4 treatments and 4 replications. P0 = control diet, P1 = control diet minus 3% ME and 3% PK, P2 = P0 + vitamin E 200 ppm, P3 = P1+ vitamin E 200 ppm. The data were analysed using ANOVA with an interaction’s significant difference test. The results showed that there was an interaction effect between supplementation with 200 ppm vitamin E and different nutrient contents on feed consumption (P<0.05). Supplementation of vitamin E (200 ppm) in the control diet according to Cobb’s recommendation gave the highest feed consumption. A decrease in the metabolizable energy (90,50 kcal kg-1) and crude protein (7.2%) of the diet (P1) significantly decreased (P<0.05) the final body weight, body weight gain and feed efficiency. Supplementation with 200 ppm vitamin E significantly (P<0.05) decreased the leukocyte count. In conclusion, reducing the metabolic energy and protein content of the diet reduced chicken growth by 10.40% and feed efficiency by 7.24%. Supplementation of vitamin E in the diet has a good effect on immunity and reduces leukocytes. According to the Cobb broiler standard (2018), the IPB-D3 chicken strain still responds to a diet that contains nutrients supplemented with 200 ppm vitamin E, which results in good performance and production